How Party Systems Shape Local–National Gender Gaps. Issue 1 (4th December 2017) - Fortin-Rittberger, Jessica; Eder, Christina; Kroeber, Corinna; Marent, Vanessa
Abstract : Women's representation is highest in local assemblies in some countries, while others display the largest share of female office-holders at the national level. Drawing on a new data set mapping the representation of women at all four levels of government in Germany during the 2000s, we argue that differences in party system configurations across echelons explain these distinct patterns and provide evidence for this claim. We show that left-wing parties, the main source of female office-holders, perform better at higher echelons, while minor parties and independent representatives, which favour male candidacy, win more seats at the lowest levels of government.